Analisis Faktor yang Mempengaruhi Kejadian Unmet Need pada Pasangan Usia Subur (PUS) di Kecamatan Pahandut Kota Palangkaraya: Analysis of Factors that Influence Unmet Need in Childbearing Age Couples in Pahandut District Palangkaraya City - Septian Mugi Rahayu; Erlina Cahayani (Jurnal Surya Medika (JSM), 2022)
In Central Kalimantan Province, especially in Palangka Raya, there are still sexually active couples of childbearing age and reporting want to delay having children or do not want to have more children but have not used contraceptives which are often referred to as unmet needs, as evidenced by the unmet need tolerance target in 2020, which was set at 5.73% and could only be achieved at 11.9%, this can be seen in the Radalgram date of December 2020, the National Population and Family Planning Agency (BKKBN) of Central Kalimantan Province. Analyzing the factors that influence the incidence of unmet needs in couples of childbearing age in Pahandut District, Palangka Raya City. Correlational descriptive with Cross Sectional approach. The population of this research is couples of childbearing age who are included in the category of unmet needs in Pahandut District, Palangka Raya city, totaling 2.383. The number of samples to be taken is as many as 357. The sampling technique used purposive sampling. The data was collected by a questionnaire. Data were analyzed by Chi-Square (α = > 0.05). From the results of the study, it can be seen that there is a correlation between the age of the wife and the incidence of unmet need (p = <.0001), there is a correlation between access to health facilities and the incidence of unmet need (p = 0.037), there is a correlation between husband's support and the incidence of unmet need. (p=0.007), there is a relationship between myths about family planning and the incidence of unmet needs (p=0.002). The factors of education level, wife's knowledge, wife's occupation, economic status, parity, and family planning history are not related to the incidence of unmet needs.